Inflammatory cytokines and stroke and its subtypes: a genetic correlation and two-sample Mendelian randomization study - Guo, Yu; Sun, Huaiyu; Hou, Shuai; Zhang, Wuqiong; Liu, Huiqing; Zhu, Lixia; Meng, Hongmei (Frontiers in Molecular Neuroscience, 2023)
The causal relationship between inflammatory factors and stroke subtypes remains unclear. This study aimed to analyze the causal relationship between 41 inflammatory factors and these two factors using Mendelian randomization (MR).We performed a two-sample MR analysis to assess the causal effects of 41 inflammatory cytokines on stroke and its subtypes and conducted a genome-wide association study (GWAS) data. The inverse-variance weighted (IVW) method was adopted as the main MR method, and we performed a series of two-sample Mendelian randomizations and related sensitivity analyses. Results: The study indicated some suggestive evidences: using the IVW approach, we found that lower possible levels of IL-4 were positively associated with the occurrence of stroke (odds ratio [OR] = 0.93, 95% confidence interval [CI]:0.88-0.99, p = 0.014), higher interleukin (IL)-1β, IL-12p70 levels may be positively correlated with the occurrence of stroke (OR = 1.09, 95% CI:1.01-1.18, p = 0.027; OR = 1.08, 95% CI:1.02-1.15, p = 0.015). For IS, resultsshowed that lower levels of IL-4, tumor necrosis factor-related apoptosis-inducing ligand were positively associated with the occurrence of possible ischemic stroke (IS)